Pengaruh Lingkungan Kerja Dan Stres Kerja Terhadap Kinerja Karyawan PT. XYZ - Widyastuti Wulandari; Hasanuddin Hasanuddin (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This study aims to measure the effect of Work Environment and Job Stress on Employee Performance of PT XYZ. The population and sample amounted to 50 people or all employees of PT. XYZ. The sampling technique used in this study used saturated samples. The data collection tool in this study used a questionnaire with 50 respondents. The design used in this research is testing using SPSS for windows version 26. The results of this study indicate that the work environment has a significant positive effect on employee performance and work stress has a significant positive effect on the performance of PT. XYZ employees. This research provides advice to PT. XYZ to be able to pay more attention to workspace facilities, and pay attention to the conditions of work stress experienced by its employees so that employee performance increases.